The importance of nutrition in the course of celiac disease - Jadwiga Janina Bednarek (Kazimierz Wielki University, 2018)
Celiac disease is one of the most common autoimmune diseases.It is estimated that it is the cause of health disorders in about 1% of the general population.It is increasingly diagnosed in adults.New diseases affect about 60% of this group, of which 15-20% concern people>60 years of age.The pathogenesis of celiac disease is conditioned by many factors. Cereal proteins referred to collectively as gluten are an important factor that reveals the presence of celiac disease.Consumption of gluten causes an abnormal stimulation of the immune system in genetically predisposed people.Gluten-induced immune system causes the atrophy process to prevail over the regenerative processes in the small intestine. This disorder leads to atrophy of the intestinal villi. The only commonly accepted method of treating visceral disease is the elimination of gluten from food. Proper management of a lifelong disease is based on the continuous acquisition of knowledge and skills that improve the quality of life in all its spheres.